Training and retirement - Nicolai Kristensen (Institute for the Study of Labor (IZA), 2012)
This paper presents results on the effect of formal life-long learning on the decision to retire early. Specifically, I estimate an Option Value model based on individual employer-employee longitudinal data including comprehensive government co-sponsored training records dating back more than 30 years. Human capital theory predicts that the amount of training and the length of working life will be positively correlated in order to recoup investment and yield a higher return. Significant upper bound effects of training in prolonging working life are found for certain types of training and certain groups of workers. However, out-of-sample simulations indicate that on average one year of training only adds up to one month to the career length. This means that training in itself is not enough to substantially prolong careers and increase the workforce.
urn:nbn:de:101:1-201204239412
Keywords: H55; I21; J26; 330; training; retirement; option value; upper bound identification; Lebenslanges Lernen; Weiterbildung; Altersgrenze; Realoption; Erwerbsverlauf; Schätzung; Dänemark